Performance enhancement of top-level swimmers by velocity regimes modelling - Issurin, V. B.; Kaufman, L. E.; Tenenbaum, G. (Biomechanics and Medicine in Swimming VIII, 1999)
The study aimed to approve training system based on velocity regimes modeling. The threeyear sequential experiment with national class swimmers consisted of three equal annual stages. The first stage contained conventional design when velocity regimes were prescribed according to coach's experience; training program of the second and third stages consisted of modeling of training regimes developed by the authors; a "lactate-velocity" test was used in the third stage. The follow up program contained competition performance and a number of tests to evaluate performance-related abilities. Repeated Measures ANOV As were applied to examine the gains in swimming performances and specific biomotor components. ANOV A which was applied to the pre-post gain scores indicated significant differences. A multiple comparisons tests indicated that during the second (modeling) and third stages (modeling plus blood testing) swimmers progressed significantly more than during the stage with the control program. Similarly the main biomotor components developed during the second and third stages more than during the first one.